Epigenetic signatures of maternal-fetal health: insights from cord blood and placenta - Jagadeesh Puvvula; Joseph M. Braun; Emily A. DeFranco; Shuk-Mei Ho; Yuet-Kin Leung; Shouxiong Huang; Xiang Zhang; Ann M. Vuong; Stephani S. Kim; Zana Percy; Aimin Chen (Epigenetics)
The placenta is vital for fetal growth, and its methylation patterns reflect placental function, affecting the fetus and providing insights into disease origins. While cord blood methylation is convenient for assessing the fetal environment, methylation profiles vary by tissue due to variance in cell populations, function, and life stage. As tissue differences extensively contribute to the DNA methylation patterns, using surrogate samples such as cord blood may result in inconsistent findings. In this study, we aim to quantify the correlation of cytosine-phosphate-guanine dinucleotides (CpGs) between paired cord blood and placenta samples. Using the Infinium Human Methylation 450 K BeadChip, we compared methylation patterns in cord blood mononuclear cells (CBMC; n = 54), the maternally-facing side of placental tissue (MP; n = 68), and the fetal-facing side of placental tissue (FP; n = 67). Methylation patterns from the FP (6,021 CpGs) were significantly correlated with CBMC compared to the MP (2,862 CpGs). These CpGs were related to the biological (mitotic cell) process and molecular function (ribonucleoprotein complex binding). Our findings quantified CpG site correlation between cord blood and placenta, providing a valuable reference for future studies on placental health that rely on cord blood methylation in the absence of placental biospecimens.